Predictive factors of the tumor immunological microenvironment for long‐term follow‐up in early stage breast cancer. Issue 1 (21st January 2017) - Okabe, Mina; Toh, Uhi; Iwakuma, Nobutaka; Saku, Shuko; Akashi, Momoko; Kimitsuki, Yuko; Seki, Naoko; Kawahara, Akihiko; Ogo, Etsuyo; Itoh, Kyogo; Akagi, Yoshito
Abstract : The aim of this research was to investigate the correlation of immunologic factors in the tumor environment of breast cancer, using immunohistological staining to evaluate the expression of programmed death 1/programmed death ligand 1 (PD‐1/PD‐L1), phosphatase and tensin homolog (PTEN), tumor infiltrating lymphocytes (TILs), and macrophages, and to analyze the association between the immunologic factors and clinical outcome for patients with early stage breast cancer (EBC). A total of 97 EBC patients who underwent standard surgery were investigated. Expression of PD‐1/PD‐L1 and PTEN and the density of CD3 + TILs, CD8 + TILs, and CD163 + macrophages were evaluated by immunohistochemical analysis. The association between the immunologic factors and clinical outcome was statistically analyzed. The density of CD3 + TILs, CD8 + TILs, and CD163 + macrophages and non‐expression of PTEN was significantly higher in cases of triple negative breast cancer. CD8 + TIL density and CD8 + /PD‐L1 + expression were predictive factors for disease‐free survival and overall survival (OS). Human epidermal growth factor 2 (HER2)‐positive patients with PTEN expression and luminal/HER2‐negative patients without PD‐L1 expression had significantly longer OS compared to patients without PTEN expression ( P = 0.049) and with PD‐L1 expression ( P = 0.036), respectively. Furthermore, patients with PD‐L1 + /CD8 + expression had worse median progression‐free survival ( P = 0.022) and median OS ( P = 0.037) compared with patients without PD‐L1 + /CD8 + expression. The CD3 + TILs, CD8 + TILs, and CD163 + macrophages were shown to infiltrate the tumor area of EBC. In particular, triple negative breast cancer had a higher rate of TIL infiltration within the tumor environment. Expression of PTEN and lack of PD‐L1 expression were associated with favorable survival in HER2‐positive and luminal/HER2‐negative EBC patients, respectively. The PD‐L1 expression combined with CD8 + density was significantly associated with an aggressive clinical outcome. Abstract : This study demonstrated that CD3+ TILs, CD8+ TILs, and CD163+ macrophages were shown to infiltrate the early‐stage breast cancer tumor area. PTEN expression and lack of PD‐L1 expression were associated with favorable survival in Her2‐positive and luminal/Her2‐negative BC patients, respectively. The PD‐L1 expression combined with CD8+ density was significantly associated with an aggressive clinical outcome. These results suggest that immunologic factors may be a useful predictive biomarker in patients with early stage breast cancer for a long‐term follow‐up.